2012
DOI: 10.1002/anie.201203852
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Assistance in Bifunctional Organocatalysis: Enantioselective Mannich Reactions with Aliphatic and Aromatic Imines

Abstract: Hold them tight: Guided by X-ray structures, bifunctional thiourea catalysts containing an activating intramolecular hydrogen bond were redesigned. The new catalysts were used to effect a highly enantioselective Mannich reaction between malonates and both aliphatic and aromatic imines (see scheme; Boc=tert-butoxycarbonyl).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 27 publications
4
64
0
Order By: Relevance
“…162 They reported the direct Mannich reaction of malonate with N-Boc aldimine to furnish the corresponding adducts with excellent enantioselectivities. A thiourea catalyst 84 was found to be the catalyst of choice for aldimines derived from aromatic aldehyde, and 85 was suitable for aldimines derived from aliphatic aldehydes.…”
Section: Mannich-type Reactions Catalyzed By Cinchona Alkaloid-thiourmentioning
confidence: 99%
“…162 They reported the direct Mannich reaction of malonate with N-Boc aldimine to furnish the corresponding adducts with excellent enantioselectivities. A thiourea catalyst 84 was found to be the catalyst of choice for aldimines derived from aromatic aldehyde, and 85 was suitable for aldimines derived from aliphatic aldehydes.…”
Section: Mannich-type Reactions Catalyzed By Cinchona Alkaloid-thiourmentioning
confidence: 99%
“…15 The group found that catalysts that contain a rigid trans-1,2-aminoindanol scaffold and a urea group that activates the thiourea group through intramolecular hydrogen bonds (such as 9) promote the enantioselective Mannich reaction between malonates and both aliphatic and aromatic imines. This offers a useful direct route to a wide variety Scheme 9 of protected β 3 -amino acids.…”
Section: Bifunctional Organocatalysismentioning
confidence: 99%
“…1,2 Foldamers are generally considered as artificial models for molecular folding, 3 but they may also find use in enzyme-like functions, for example as biomimetic receptors 4 and catalysts 5,6,7 . The most common bond type in foldamers is the amide bond with directional and relatively stable hydrogen bonding properties.…”
Section: Introductionmentioning
confidence: 99%